2014
DOI: 10.1002/j.2161-0045.2014.00075.x
|View full text |Cite
|
Sign up to set email alerts
|

College Major Choice in STEM: Revisiting Confidence and Demographic Factors

Abstract: Using national freshman survey data, the authors examined confidence and background variables (e.g., gender, minority status, parental occupation) as predictors of science, technology, engineering, and mathematics (STEM) major choice. Logistic regression analyses revealed that students were more likely to choose STEM majors if they had strong confidence in mathematics and academic areas and had parents with STEM occupations. Although female students were unlikely to choose a STEM major, African American and La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
135
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(148 citation statements)
references
References 21 publications
(56 reference statements)
4
135
0
4
Order By: Relevance
“…The unifying conclusion is that women and racial minorities have lower selfconfidence in their ability than males or racial majorities (e.g. Moakler, Kim & Minsun, 2014;Morony, Kleitman, Lee & Stankov, 2012;London et al, 2012;Nagy, et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The unifying conclusion is that women and racial minorities have lower selfconfidence in their ability than males or racial majorities (e.g. Moakler, Kim & Minsun, 2014;Morony, Kleitman, Lee & Stankov, 2012;London et al, 2012;Nagy, et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Moakler and Kim (2014) examined the relationship between confidence and demographic information in a national survey of 335,842 college freshman and found that even women and minorities who reported above average confidence in other domains still reported lower confidence in mathematics, and their mathematical confidence levels were nearly 10% lower than males and non-minorities.…”
Section: Basic Demographicsmentioning
confidence: 99%
“…Mathematical experiences and preparation in secondary education are highly influential and are a significant driving force behind choice of major in college (Betz and Hackett 1983;Moakler and Kim 2014). Lower mathematical achievement deters students from pursuing STEM disciplines, and those who do choose STEM majors are disproportionately likely to be young, male, come from higher socioeconomic background, have a parent with a STEM degree, and have had sufficient prior preparation in science and mathematics (Wang 2013).…”
Section: Foundations Of Mathematics Self-efficacy Attitudes and Anxmentioning
confidence: 99%
See 1 more Smart Citation
“…A qualitative study of nonpersisters in engineering showed that individual factors and institutional factors influenced the students' decision to leave engineering. 4 Individual factors included: failure to integrate into engineering culture, disappointment, and feelings of being overwhelmed. Institutional factors included: inadequate high school preparation, loss of motivation to study due to program rigor, poor teaching/mentoring, inadequate advising, unwelcome culture of engineering department, financial pressures, poor academic performance, disinterested.…”
Section: Literature Reviewmentioning
confidence: 99%